2016
DOI: 10.1016/j.jvs.2016.03.467
|View full text |Cite
|
Sign up to set email alerts
|

Impact of femoropopliteal endovascular interventions on subsequent open bypass

Abstract: OBP after failed EVT was needed in a minority of patients. A change in the bypass target to a more distal site was identified in nearly half of patients. Although an endovascular-first approach to treating claudication and critical limb ischemia is safe and resulted in few progressing to OBP, poor outcomes of open interventions after EVT can be expected if EVT fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
(21 reference statements)
0
6
1
1
Order By: Relevance
“…22 In contrast with other studies, previously unsuccessful angioplasties of tibial arteries had no significant impact on primary or secondary patency, limb salvage, and survival of tibiodistal bypass. [4][5][6] The primary patency rates in our study were relatively low for vein bypasses (55% in group A vs 53% in group B) at 1 year, compared with the results of Lyon et al, 13 with 77%, or with a metaanalysis of popliteodistal bypasses with 81.5%. 23 Our own distal bypasses with more proximal inflow are also performing better with primary patency rates of approximately 80% after 1 year.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…22 In contrast with other studies, previously unsuccessful angioplasties of tibial arteries had no significant impact on primary or secondary patency, limb salvage, and survival of tibiodistal bypass. [4][5][6] The primary patency rates in our study were relatively low for vein bypasses (55% in group A vs 53% in group B) at 1 year, compared with the results of Lyon et al, 13 with 77%, or with a metaanalysis of popliteodistal bypasses with 81.5%. 23 Our own distal bypasses with more proximal inflow are also performing better with primary patency rates of approximately 80% after 1 year.…”
Section: Discussioncontrasting
confidence: 54%
“…Since the 1990s, tibial percutaneous transluminal angioplasty (PTA) is increasingly advocated and considered as feasible, safe, and effective in critical limb ischemia (CLI) 1 with similar outcomes compared with bypass surgery. 2,3 In contrast, there is growing evidence of inferior outcome in patients undergoing bypass surgery after failed infrainguinal PTA [4][5][6] and poorer wound healing after infrapopliteal PTA compared with bypass surgery. 7,8 Some authors prefer an endovascular first approach, 9 whereas the American College of Cardiology Foundation/American Heart Association stated that a bypass surgery first approach is reasonable in CLI patients with a life expectancy of more than 2 years and useable vein grafts.…”
mentioning
confidence: 99%
“…Although BASIL trial data are often said to be outdated and so no longer relevant to current practice, in reality, there is no evidence that is the case. 8 For example, Darling and colleagues recently studied 2869 patients undergoing lower limb revascularisation for CLTI and concluded that PB resulted in better outcomes in wound healing, FFR, and OS; and that patients undergoing SB had higher rates of further intervention. 14 In another study, Jones and co-workers analysed 1154 CLTI patients undergoing SB and concluded that these patients had worse MALE, FFR, OS, and AFS.…”
Section: Discussionmentioning
confidence: 99%
“…20,26 Gifford et al looked at the impact of change in distal target and found that 43% of patients undergoing bypass after failed endovascular therapy had the location of the distal target changed to a more distal location compared with the pre-endovascular intervention angiography. 34 Joels et al, in a small retrospective study, evaluated change in distal bypass site after endovascular intervention of the superficial femoral artery as judged by three operators in a blinded manner. 3 They found that 41% of patients with critical limb ischaemia required a change in distal target site after a failed endovascular intervention.…”
Section: Primary Bypass Bypass After Failed Evt Odds Ratio Weight M-hmentioning
confidence: 99%
“…Others have argued that failure of any intervention may result from systemic effects such as latent hypercoagulability, propensity for neointimal hyperplasia, or aggressive atherosclerosis. 18,26,34,35 However, not all the data support this as Nolan et al found that prior contralateral revascularisation was not a risk factor for worse outcomes following subsequent bypass, indicating that local factors (conduit, runoff, distal target) are probably more important. 26 The presence of marginal vein quality at the time of the initial revascularisation has also been implicated, as this may lead an interventionalist to favour an initial endovascular procedure but limits the options for subsequent autogenous bypass.…”
Section: Primary Bypass Bypass After Failed Evt Odds Ratio Weight M-hmentioning
confidence: 99%